Seleksi Penerimaan Bantuan Internet Gratis dengan Menggunakan Metode AHP - Tukino Paryono; Muhamad Rizky Arfani; Agustia Hananto; Baenil Huda (Masoem University, 2023)
The internet is an information technology that is able to provide benefits for life and is a major requirement as a means of communication, entertainment or business. Covid 19 spreads throughout the City or Regency to villages in all regions in Indonesia which has a broad impact on the world of Education, especially Elementary and Middle School Education. Seeing the change in learning patterns from face-to-face to online learning, there are obstacles that are felt by students, especially in learning that requires the teaching and learning process between teachers and students to be carried out remotely (online). To support online learning, adequate internet facilities are needed. Provision of internet packages can be provided free of charge with due observance of predetermined requirements. To support the provision of free internet packages, a decision support system is needed to determine the selection of receiving free internet assistance so that it is right on target by using the Analytical Hierarchy Process (AHP) solving procedure. This method is used to make rankings for selecting free internet recipients, where the highest score is generated based on the best criteria. The results of calculations with this method. Where to make a decision support system in order to prevent errors in determining the criteria that deserve free internet assistance.